FACTORS INFLUENCING THE INTENTION TO USE E-GOVERNMENT SERVICES IN ALGERIA: AN EMPIRICAL STUDY - DJERMANI, Farouk; SHAHZAD, Arfan; SHEIKH, Adnan Ahmed; ALEKAM, Jamal Mohammed Esmail (Studia Universitatis Babeș-Bolyai Negotia, 2016)
The purpose of this paper is to investigate about behavioral intention of an Algerian citizen to use e-government services and also to see certain factors effecting to use these services. The research model includes; subjective norms and behavioral intention to use e-government services have been developed based on the technology acceptance model (TAM), which is supported by the theory of reasoned action (TRA) and theory of planned behavior (TPB). The overall framework has been applied to understand the intention to use e-government services in the context of Algeria. Furthermore, there are two independent variables family and media, which influence through mediation i.e. subjective norm on the dependent variable of intention to use e-government services. The study used 300 questionnaires, which was sent to Algerian students, 100 respondents have replied, which is about 33% response. However, the findings of this research analysis have shown that, family influence has a direct, positive and significant relationship towards intention to use e-government services, whereas media influence is significant towards intention to use e-government services with the mediation of subjective norm. Consequently, subjective norm mediates positively in the relationship between family influence and intention to use e-government. Thus, the contribution made by this study is to provide further insight and a better understanding of citizens of Algeria to use e-government services. The study represents a guideline for establishing an appropriate model for e-government adoption of citizens’ perspectives.